Plate-like alumina powder, its manufacturing method, and paint or cosmetic
Patent Information
- Application Number
- JP2024055267
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-03-29
AI Technical Summary
【0025】 本発明によれば、分散性に優れた板状アルミナ粉末及びその製造方法が提供される。また、前記板状アルミナ粉末を含む塗料又は化粧品が提供される。
Smart Images

Figure 0007643614000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a platelet alumina powder, a method for producing the same, and a paint or cosmetic. [Background technology]
[0002] Alumina (Al2O3) is chemically stable and has excellent heat resistance, corrosion resistance, wear resistance, and insulation properties, as well as high strength and hardness. Taking advantage of these characteristics, alumina powder is widely used in a variety of applications, including structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories.
[0003] In particular, plate-like alumina powder has a high light reflectance and high brightness on its particle surface. Therefore, taking advantage of this characteristic, it is used as a pigment added to paints and cosmetics. Note that plate-like alumina powder is a powder composed of plate-like alumina particles, and is also called scaly alumina powder, thin flaky alumina powder, flat alumina powder, or alumina flakes.
[0004] As a document disclosing the use of platelet alumina powder as a pigment, Patent Document 1 discloses a platelet alumina powder having a thickness of 500 nm or more and a D of 15 to 30 μm. 50 value and D of 30 to 45 μm 90 It is disclosed that Al2O3 flakes having a value of 0.1 to 1.0, which simultaneously have high chemical stability, a smooth surface, and high whiteness, are used as a pigment substrate (claim 1,
[0010] and
[0015] of Patent Document 1). Patent Document 1 also describes that the Al2O3 flakes are coated with a high refractive index layer such as TiO2 or a low refractive index layer such as SiO2, which gives them increased luster, interference color, or color flop effect (
[0040] to
[0046] of Patent Document 1).
[0005] Patent Document 2 discloses a paint composition containing alumina flakes as a luster pigment, and describes that it can be suitably used as an automobile top coat, and that it forms a composite coating film with unprecedented high luster and novel designability without compromising the finished appearance (claim 1,
[0001] and
[0108] of Patent Document 2). Patent Document 2 also describes that the alumina flakes are aluminum oxide (Al2O3) coated with a metal oxide such as titanium dioxide, with a particle size of 10 to 30 μm and a thickness of 0.3 to 0.4 μm (
[0007] of Patent Document 2).
[0006] Patent Document 3 discloses a pearlescent pigment containing aluminum oxide and zinc oxide as main components in a mass ratio of 100:0.1-5, and containing flaky alumina crystals coated with metal or metal precursor particles (claim 1 of Patent Document 3). Patent Document 3 also describes that the crystals have an average particle thickness of 0.5 μm or less, an average particle size of 15 μm or more, and an aspect ratio of 50 or more, and therefore have excellent gloss (
[0001] of Patent Document 3).
[0007] Patent Document 4 discloses a method for producing a plate-like alumina-based powder characterized by having a crystal structure of only α-, β-, or γ-alumina, or two or more types of crystal structures, by firing plate-like boehmite at 400° C. to 1500° C. (Claim 2 of Patent Document 4). Patent Document 4 also discloses that a cosmetic product with a good feel can be obtained by surface-coating plate-like boehmite or plate-like alumina powder with a hydrophobic compound such as polysiloxane and incorporating the coated powder into a cosmetic product (
[0013] of Patent Document 4).
[0008] Patent Document 5 discloses hexagonal plate-like alumina obtained by firing hexagonal plate-like boehmite at temperatures of 450 to 1500°C. The hexagonal plate-like alumina has a roughly hexagonal plate shape, a ratio of the major axis to the minor axis of 1 to 1.3, and an aspect ratio of 40 to 100. The document describes that the hexagonal plate-like alumina has high orientation, reduces diffuse reflection, and enhances brilliance, and can also be suitably used as a filler for the purpose of increasing the brilliance of paints and cosmetics (Claim 4 and
[0045] of Patent Document 5).
[0009] Patent Document 6 discloses plate-like alumina particles having a thickness of 0.01 to 5 μm, an average particle diameter of 0.1 to 500 μm, an aspect ratio (the ratio of the particle diameter to the thickness) of 2 to 500, a polygonal plate shape, and containing molybdenum within the particles (Claim 1 of Patent Document 6). Patent Document 6 also discloses that the plate-like alumina particles can be suitably used for thermally conductive fillers, cosmetics, abrasives, high luster pigments, lubricants, substrates for conductive powders, ceramic materials, and the like (
[0101] of Patent Document 6). [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2014-218424 A [Patent Document 2] Japanese Patent Application Publication No. 10-298458 [Patent Document 3] Special Publication No. 2010-502774 [Patent Document 4] JP 2012-071996 A [Patent Document 5] JP 2003-002642 A [Patent Document 6] JP 2019-123664 A Summary of the Invention [Problem to be solved by the invention]
[0011] Thus, the use of plate-like alumina powder as a pigment in paints and cosmetics has been proposed in the past. However, there is room for improvement in conventional plate-like alumina powders. That is, pigments are used in a state dispersed in a vehicle containing a solvent or a resin. Pigments used for such purposes are desired to have transparent crystals, excellent plate-like properties, and excellent dispersibility. In particular, pigments used for cosmetics are strongly desired to have high dispersibility. This is because the higher the dispersibility of the pigment, the more transparent the cosmetics can be.
[0012] However, conventional plate-like alumina powders have been insufficient in meeting the above-mentioned demands, particularly in that the conventional plate-like alumina powders have limitations in terms of improving dispersibility, making it difficult to further improve the transparency when used in applications such as cosmetics.
[0013] In view of these problems, the present inventors have conducted extensive research and have found that a plate-like alumina powder having a specific average particle size and average thickness and containing a large number of plate-like particles with a high degree of circularity has excellent dispersibility.
[0014] The present invention was completed based on these findings, and an object of the present invention is to provide a plate-like alumina powder having excellent dispersibility and a method for producing the same, as well as a paint or cosmetic containing the plate-like alumina powder. [Means for solving the problem]
[0015] The present invention encompasses the following aspects (1) to (9). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."
[0016] (1) A plate-like alumina powder composed of a plurality of plate-like α-alumina particles, having an average particle size of 2 μm or more and 100 μm or less and an average thickness of 0.2 μm or more and 3.0 μm or less, The plate-like alumina powder has a number ratio (high circularity particle ratio) of particles having a circularity of 0.953 or more (high circularity alumina particles) of 25% or more when the plate-like alumina powder is analyzed by a dry particle image analyzer.
[0017] (2) The plate-like alumina powder according to (1) above, wherein the average particle diameter is from 5 μm to 50 μm, the average thickness is from 0.3 μm to 1.0 μm, and the proportion of highly circular particles is 40% or more.
[0018] (3) The plate-like alumina powder according to (1) or (2) above, containing an alkali metal (AM) in an amount of 0.01% by mass or more and 0.5% by mass or less, calculated as AM2O, and containing silicon (Si) in an amount of 0.01% by mass or more and 0.3% by mass or less, calculated as SiO2.
[0019] (4) The plate-like alumina powder according to (3) above, wherein the alkali metal (AM) is one or both of sodium (Na) and potassium (K).
[0020] (5) A method for producing a plate-like alumina powder according to any one of (1) to (4) above, comprising the following steps: Preparing a raw material mixture containing aluminum hydroxide powder and an additive; and Firing the raw material mixture at a temperature of 900° C. or more and 1300° C. or less; Equipped with The raw material mixture contains alkali metal (AM) in an amount of 0.01 mass% or more and 0.5 mass% or less, calculated as AM2O, silicon (Si) in an amount of 0.01 mass% or more and 0.3 mass% or less, calculated as SiO2, and fluorine (F) in an amount of 0.1 mass% or more and 5.0 mass% or less, calculated as F.
[0021] (6) The method according to (5) above, wherein the additive comprises an alkali silicofluoride (AM2SiF6), or aluminum fluoride (AlF3) and silicon oxide (SiO2).
[0022] (7) The method according to (5) or (6) above, wherein the additive further comprises one or both of an oxide (AM2O) and a carbonate (AM2CO3) of an alkali metal (AM).
[0023] (8) The method according to any one of (5) to (7) above, wherein the alkali metal (AM) is one or both of sodium (Na) and potassium (K).
[0024] (9) A paint or cosmetic comprising the platelet alumina powder according to any one of (1) to (4) above. Effect of the Invention
[0025] According to the present invention, there are provided a platelet alumina powder having excellent dispersibility and a method for producing the same, and a paint or cosmetic containing the platelet alumina powder. [Brief description of the drawings]
[0026] [Figure 1] The mechanism by which platelet alumina powder creates a shiny appearance is shown below. [Diagram 2] 1 is a diagram for explaining circularity. [Diagram 3] 4 shows the results of measuring the zeta potential of plate-like alumina powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] A specific embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described below. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention. In addition, in this specification, any combination of suitable aspects can be adopted as long as technical consistency can be achieved. For example, one of the suitable numerical ranges can be combined with the other.
[0028] <<1. Plate-shaped alumina powder>> The plate-like alumina powder of this embodiment is composed of a plurality of plate-like α-alumina particles, has an average particle diameter of 2 μm to 100 μm and an average thickness of 0.2 μm to 3.0 μm, and when the plate-like alumina powder is analyzed by a dry particle image analyzer, the number ratio (high circularity particle ratio) of particles having a circularity of 0.953 or more (high circularity alumina particles) is 25% or more.
[0029] The plate-like alumina powder of this embodiment (hereinafter, sometimes simply referred to as "alumina powder") is composed of a plurality of plate-like alpha-alumina (Al2O3) particles (hereinafter, sometimes simply referred to as "alumina particles", "plate-like particles", or "particles"). That is, it contains plate-like alpha-alumina particles as a main component. Here, the plate-like alpha-alumina particles are particles made of alpha-alumina (corundum). Alpha-alumina has trigonal corundum crystals, and is excellent in chemical stability, heat resistance, corrosion resistance, wear resistance, and insulation, and has high strength and hardness. In addition, it has high light reflectance, brightness, and whiteness. Since the alumina powder of this embodiment contains plate-like alpha-alumina particles as a main component, it is possible to fully utilize these characteristics.
[0030] In this specification, powder means an aggregate of many independent particles. In other words, many particles aggregate to form a powder. Since each particle that constitutes a powder is independent, the powder exhibits overall fluidity in its own state. It is sufficient that most of the particles that constitute a powder are independent. As long as the powder exhibits overall fluidity, some particles may be bonded to form aggregates. In addition, an aggregate of many particles dispersed in a medium such as a liquid or resin is also called a powder.
[0031] In the plate-like alumina powder of this embodiment, the shape of the alumina particles constituting the plate-like alumina powder is plate-like (scale-like, thin-flaky, flat, flake-like). That is, each particle has a large plate surface and a small plate thickness. Specifically, the average particle diameter of the plate-like alumina powder is 2 μm or more and 100 μm or less, and the average thickness is 0.2 μm or more and 3.0 μm or less. Here, the average particle diameter and the average thickness are the average values of the particle diameter and thickness of each particle constituting the alumina powder based on the number of particles. In addition, the particle diameter is the long diameter of the particle. In other words, the long axis diameter of the particle plate surface is the particle diameter. In addition, the thickness is the plate thickness of the plate surface. The particle diameter and thickness can be obtained by observing the particles constituting the alumina powder with a scanning electron microscope (SEM). In other words, the average particle diameter and the average thickness are values obtained by SEM observation. In addition, the average particle diameter is usually larger than the average thickness.
[0032] In this way, by using particles with large plate surfaces and small plate thickness, the brilliance of the alumina powder can be increased. This point will be explained with reference to FIG. 1. As shown in FIG. 1, when a powder containing particles with large plate surfaces and small plate thickness is formed on a substrate by a method such as coating, the particle plate surfaces with large areas tend to be oriented so that they are aligned parallel to the substrate surface. The larger the particle diameter, the larger the surface area of the particle plate surfaces aligned parallel to the substrate surface. Furthermore, light incident from the outside is reflected by the particle plate surfaces and radiated to the outside as reflected light. Therefore, the larger the particle diameter, the easier it is for the incident light to be reflected by the particle plate surfaces, resulting in a higher visual brilliance.
[0033] If the average particle size is less than 2 μm or the average thickness is more than 3.0 μm, the brilliance of the powder may be insufficient. On the other hand, if the average particle size is more than 100 μm or the average thickness is less than 0.2 μm, it is difficult to manufacture the powder. In addition, the strength is low and handling is difficult. The average particle size of the plate-like alumina powder is preferably 5 μm or more and 50 μm or less, and the average thickness is preferably 0.3 μm or more and 1.0 μm or less.
[0034] The average aspect ratio of the alumina powder is preferably 20 or more and 50 or less. Here, the average aspect ratio is the ratio of the average particle diameter to the average thickness (average particle diameter / average thickness). By making the average aspect ratio 25 or more, it is possible to further enhance the brilliance of the powder. Also, by making the average aspect ratio 50 or less, the strength of the alumina powder is increased and handling becomes easier.
[0035] It is not necessary that all particles constituting the alumina powder are plate-like alpha-alumina particles. As long as the alumina powder as a whole satisfies the above-mentioned requirements for the average particle size and average thickness, it may contain particles other than plate-like alpha-alumina particles. However, in order to take advantage of the excellent effects based on the plate-like alpha-alumina particles, it is preferable that the content of the plate-like alpha-alumina particles is high. The content of the plate-like alpha-alumina particles is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more.
[0036] When the alumina powder of this embodiment is analyzed by a dry particle image analyzer, the number ratio of high circularity alumina particles (high circularity particle ratio) is 25% or more. Here, the high circularity alumina particles are plate-like α-alumina particles with a circularity of 0.953 or more. Circularity is a numerical value indicating how close to a perfect circle it is, and in principle, is 1.000 or less. As shown in FIG. 2, the circularity of a perfect circle is 1, and the further away from the perfect circle it is, the smaller the circularity becomes. For example, the circularity of a regular hexagon is 0.9523, and the circularity of a square is 0.89.
[0037] The alumina powder of this embodiment contains a large number (25% or more) of particles (high circularity alumina particles) whose plate surface shape is close to a circle. As a result, it has various advantageous effects. First, this alumina powder has the effect of excellent dispersibility. This is because the contact area between high circularity particles is small, so there is little physical contact between the particles and the interference caused by it, and problems such as aggregation are unlikely to occur. In addition, the alumina powder of this embodiment has the effect of imparting excellent transparency when used as an inorganic pigment. This is because the high circularity particles do not have sharp angles, so diffuse reflection that reduces transparency is unlikely to occur. Furthermore, the alumina powder of this embodiment has the effect of being less likely to damage other members. This is because the high circularity particles do not have sharp angles, so there is little risk of damage (scratch) even if they come into contact with other members.
[0038] In contrast, if the proportion of highly circular particles is low (less than 25%), dispersibility is poor and there is a risk of problems in terms of transparency, etc. For example, particles with low circularity, such as polygonal plate-like particles, are prone to physical interference with other particles and therefore have low dispersibility. In addition, the corners of the particles are easily chipped during post-processing. The chipped particle corners are prone to diffuse reflection, which deteriorates transparency. Another problem is that the corners of the particles are prone to scratch other components such as processing equipment.
[0039] From the viewpoint of utilizing the excellent effect based on the high circularity particles, it is desirable that the ratio of high circularity particles (the ratio by number of high circularity alumina particles) is high. The ratio by number is preferably 30% or more, more preferably 35% or more, and even more preferably 40% or more. There is no upper limit to the ratio by number, and it is sufficient that it is 100% or less. The ratio by number may be 90% or less, 80% or less, 70% or less, or 60% or less.
[0040] The proportion of high circularity particles is obtained as follows. First, the alumina powder is analyzed using a dry particle image analyzer. As the dry particle image analyzer, for example, a fully automatic image type particle size distribution analyzer (Spectris Corporation, Morphologi 4) or a device equivalent thereto is used. During the analysis, the particle morphology is evaluated based on the two-dimensional projected image of each particle constituting the alumina powder. Specifically, the area (s) and perimeter (l) of the particle are measured in the two-dimensional projected image. Then, the perimeter (lc) of the equivalent area circle of this particle is obtained. Here, the equivalent area circle is a virtual circle having an area equal to the area (s) of this particle. The perimeter (lc) of the equivalent area circle is obtained from the area (s) of the particle according to the following formula (1). Then, the circularity of each particle is obtained from the perimeter (l) of the particle and the perimeter (lc) of the equivalent area circle according to the following formula (2).
[0041]
number
[0042] Then, the number of analyzed particles and the number of particles with a circularity of 0.953 or more (high circularity alumina particles) are counted, and the number ratio (number of high circularity alumina particles / number of analyzed alumina particles) is calculated as the high circularity particle ratio.
[0043] The alumina powder of this embodiment preferably contains an alkali metal (AM) in an amount of 0.01% by mass or more and 0.5% by mass or less in terms of AM2O, and silicon (Si) in an amount of 0.01% by mass or more and 0.3% by mass or less in terms of SiO2. The content of the alkali metal (AM) is more preferably 0.01% by mass or more and 0.3% by mass or less in terms of AM2O. The content of silicon (Si) is more preferably 0.01% by mass or more and 0.2% by mass or less in terms of SiO2. The alkali metal (AM) is preferably one or both of sodium (Na) and potassium (K). By including these components, it is possible to further enhance the brilliance of the alumina powder.
[0044] The alumina powder of the present embodiment preferably contains at least aluminum (Al), an alkali metal (AM), silicon (Si), and oxygen (O). However, other components (elements other than Al, AM, Si, and O) may be contained as long as the above-mentioned requirements are satisfied. Furthermore, the presence of impurities that are inevitably mixed in during the manufacturing process is permitted. One such other component is fluorine (F). Fluorine (F) is a component derived from an additive added during the manufacture of the alumina powder. That is, as described later, the additive added during the manufacture of the alumina powder contains fluorine (F). Most of the fluorine volatilizes during the firing process, but some may remain. The amount of fluorine in the alumina powder is typically 0.5% by mass or less, 0.3% by mass or less, or 0.1% by mass or less.
[0045] If other components (elements other than Al, AM, Si, and O) are contained in large amounts, the brilliance of the alumina powder may be impaired. Therefore, the content of other components is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and most preferably 0.1% by mass or less. In particular, since iron (Fe) has the effect of coloring the alumina powder, it is preferable to suppress its content. Preferably, the content of iron (Fe) is 0.05% by mass or less in terms of iron oxide (Fe2O3).
[0046] The specific surface area (S BET ) is 0.1m 2 / g or more 5.0m 2 / g or less is preferable, and 0.5m 2 / g or more 2.0m 2 / g or less is more preferable. If the specific surface area is too large, the particle size of the alumina powder becomes small, which may reduce the sense of brilliance. On the other hand, it is difficult to produce an alumina powder with a small specific surface area.
[0047] The alumina powder of this embodiment has high chemical stability because it is mainly composed of α-alumina. In addition, it has a large average particle size and excellent dispersibility. Alumina powders with such characteristics are suitable for use in the fields of paints and cosmetics. However, the alumina powder of this embodiment is not limited to those used in paints and cosmetics. It can be used in known applications such as reinforcing materials and gas barrier materials mixed into plastics and resin films, structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories.
[0048] <<2. Manufacturing method of plate-shaped alumina powder>> The manufacturing method of the plate-like alumina powder of this embodiment is not limited as long as it satisfies the above-mentioned requirements. However, it is preferably manufactured by the following procedure. A preferred manufacturing method includes a step of preparing a raw material mixture containing aluminum hydroxide powder and additives (raw material mixing step), and a step of firing this raw material mixture at a temperature of 900°C to 1300°C (firing step). The raw material mixture contains an alkali metal (AM) in an amount of 0.01% by mass to 0.5% by mass calculated as AM2O, silicon (Si) in an amount of 0.01% by mass to 0.3% by mass calculated as SiO2, and fluorine (F) in an amount of 0.1% by mass to 5.0% by mass. If necessary, a post-treatment step may be provided after the firing step.
[0049] The manufacturing method of this embodiment is particularly characterized in that aluminum hydroxide powder is used as a raw material and the composition of the raw material mixture is controlled within a specific range, and this characteristic makes it possible to obtain an alumina powder that has a desired size and contains a large amount of highly circular alumina particles, resulting in excellent dispersibility. Each step will be described in detail below.
[0050] <Raw material mixing process> In the raw material mixing step, a raw material mixture containing aluminum hydroxide powder and additives is prepared. Aluminum hydroxide is a compound represented by the chemical formula Al(OH)3, and is dehydrated by heating to change into α-type aluminum oxide (α-alumina). Two types of aluminum hydroxide are known: gibbsite (γ-type aluminum hydroxide) and bayerite (α-type aluminum hydroxide). In this embodiment, either gibbsite or bayerite may be used. However, a powder made of thermodynamically stable gibbsite is preferable.
[0051] As long as the alumina powder of the present embodiment can be obtained, the size of the aluminum hydroxide powder as the raw material is not particularly limited. However, the volume average particle size (D50) is preferably 0.5 μm or more and 15 μm or less. Alternatively, the specific surface area (S BET ) is 0.5m 2 / g or more 20m 2 / g or less. D50 is the cumulative 50% diameter in the particle size distribution on a volume basis determined by a laser diffraction / scattering particle size distribution analyzer. BET is a value obtained by measurement using the N2 gas adsorption method.
[0052] The additive is a component that becomes liquid in the subsequent firing step and acts as a mineralizer. The additive contains at least silicon (Si) and fluorine (F), and may further contain an alkali metal (AM) as necessary. As described later, when the composition of the liquid phase component is appropriately controlled, the crystallization and grain growth of the alumina particles proceeds appropriately, and as a result, it is possible to obtain an alumina powder having a desired size and containing a large amount of highly circular alumina particles.
[0053] Therefore, in order to obtain an alumina powder with excellent dispersibility, it is important to appropriately control the composition of the raw material mixture containing additives. Specifically, the composition of the additives is adjusted so that the raw material mixture contains an alkali metal (AM) of 0.01 mass% or more and 0.5 mass% or less in terms of AM2O, silicon (Si) of 0.01 mass% or more and 0.3 mass% or less in terms of SiO2, and fluorine (F) of 0.1 mass% or more and 5.0 mass% or less in terms of F. When the composition of the raw material mixture is within the above-mentioned range, an alumina powder with excellent dispersibility, which contains many alumina particles with a large average particle size and high circularity, can be obtained. On the other hand, if the raw material mixture composition is inappropriate, it may have a negative effect on the particle size and the content ratio of high circularity alumina particles.
[0054] The amount of alkali metal (AM) in the raw material mixture is more preferably 0.01% by mass or more and 0.5% by mass or less in terms of AM2O. The alkali metal is preferably one or both of sodium (Na) and potassium (K). The amount of silicon (Si) in the raw material mixture is more preferably 0.05% by mass or more and 0.15% by mass or less in terms of SiO2. The amount of fluorine (F) in the raw material mixture is more preferably 0.1% by mass or more and 1.0% by mass or less in terms of F. By limiting the composition of the raw material mixture to within the above-mentioned range, the content ratio of high circularity alumina particles can be further increased, and as a result, it is expected that an alumina powder with even better dispersibility can be obtained.
[0055] The additive contains at least silicon (Si) and fluorine (F). The additive may or may not contain an alkali metal (AM). The raw aluminum hydroxide powder may contain an alkali metal (AM) as an impurity. When the amount of alkali metal in the aluminum hydroxide powder is sufficient, the additive may not contain an alkali metal. On the other hand, when the amount of alkali metal in the aluminum hydroxide powder is insufficient, it is preferable to add an alkali metal as an additive. Furthermore, the additive may contain aluminum (Al). When the additive contains aluminum, this aluminum is incorporated into the alumina powder during the firing process.
[0056] As long as an alumina powder having a desired size and containing a large amount of highly circular alumina particles can be obtained, the additive may contain other components other than alkali metals (AM), silicon (Si), fluorine (F), aluminum (Al) and oxygen (O). However, if the amount of other components is excessively large, it may adversely affect the particle size and the content ratio of highly circular alumina particles. The content of other components is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 1% by mass or less. The additive may not contain other components other than alkali metals (AM), silicon (Si), fluorine (F), aluminum (Al) and oxygen (O) in amounts exceeding the impurity amount.
[0057] According to a preferred embodiment, the additive contains aluminum fluoride (AlF3) and silicon oxide (SiO2). When the amount of alkali metal in the aluminum hydroxide powder is insufficient, it is preferred that the additive further contains one or both of an oxide (AM2O) and a carbonate (AM2CO3) of an alkali metal (AM). According to another preferred embodiment, the additive contains an alkali silicon fluoride (AM2SiF6). By using an appropriate amount of these compounds (AlF3, SiO2, AM2O, AM2CO3, AM2SiF6) as additives, it is possible to reliably produce an alumina powder having a desired size and containing a large amount of highly circular alumina particles. In addition, these compounds are inexpensive and easily available. Therefore, a plate-shaped alumina powder can be obtained at a lower cost.
[0058] The raw material mixture may be prepared by mixing aluminum hydroxide powder and additives. The mixing may be performed by a known method. It may be performed in a dry manner or a wet manner. Dry mixing may be performed using a dry mixer such as an air blender, a V-type blender, a rocking blender, a Henschel mixer, or a Nauta mixer. In the case of wet mixing, a solvent such as water is added to the aluminum hydroxide powder and additives to form a slurry, and the obtained slurry may be mixed using a wet mixer such as a ball mill, an attritor, or a bead mill.
[0059] <Firing process> In the firing process, the resulting raw material mixture is fired at a temperature between 900°C and 1300°C to obtain a fired product. During firing, aluminum hydroxide (Al(OH)3) is dehydrated and transformed into alpha-alumina (Al2O3). Additionally, the alkali metals (AM), silicon (Si) and fluorine (F) in the raw material mixture become liquid oxides and act as mineralizers to promote the crystallization of alpha-alumina. In other words, the crystal structure changes during the transition from Al(OH)3 to alpha-alumina. The addition of mineralizers promotes the crystallization of alpha-alumina (corundum), making it possible to lower the transition temperature.
[0060] The mineralizer components (AM, Si, F) that become liquid during firing cover the surface of the alumina particles, and some of them penetrate into the inside of the particles. This liquid phase component has the function of promoting the diffusion and growth of particles. That is, some of the aluminum atoms (Al) from the surface of the alumina particles dissolve into the liquid phase, and the dissolved aluminum precipitates in another place on the particle surface. This causes the growth of the alumina particles. At this time, depending on the composition of the liquid phase component, a difference occurs in the growth direction of the alumina particles, and the growth rate changes. Therefore, if the composition of the liquid phase component is appropriately adjusted, the growth of the aluminum particle plate surface is controlled, and as a result, particles with high circularity are obtained. The liquid phase component also has the effect of smoothing the plate surface of the alumina particles. If the alumina particle surface has unevenness, the unevenness will preferentially diffuse into the liquid phase, and the unevenness will disappear. Therefore, if the composition of the liquid phase component is appropriately controlled, it is possible to obtain an alumina powder with excellent dispersibility that has a desired size, a smooth surface, and a high circularity of alumina particles.
[0061] If the firing temperature is less than 900°C, the transition to α-alumina and grain growth may be insufficient. Therefore, it may be difficult to obtain alumina powder with excellent dispersibility. On the other hand, if the firing temperature is more than 1300°C, the particles may sinter together to form a strong sintered mass. In addition, the energy consumption for firing may be excessive, which may lead to an increase in manufacturing costs. The firing temperature is preferably 1000°C or more and 1200°C or less, more preferably 1000°C or more and 1100°C or less. In addition, the firing time is preferably 10 hours or more and 20 hours or less. This makes it possible to reliably ensure the transition to α-alumina and grain growth while preventing excessive sintering of the particles. The firing furnace is not limited as long as the desired alumina powder is obtained. However, from the viewpoint of effectively exerting the action of the additive during firing, a stationary furnace capable of firing using a closed firing container is preferable.
[0062] <Post-processing> If necessary, the fired product obtained through the firing process may be subjected to post-treatment such as soda removal, crushing, and / or classification. In the soda removal treatment, excess alkali metal components attached to the fired product surface are removed. This allows the amount of alkali metal in the finally obtained alumina powder to be adjusted. The alkali metal components on the particle surface can be removed, for example, by washing and filtering the fired product. In the crushing treatment, mild mechanical energy is applied to the fired product to break the bonds of the aggregated particles formed during firing. The crushing treatment can be performed in a dry or wet manner using a crusher such as a pot mill, a pin mill, and / or a jaw crusher. In the classification treatment, particles are selected according to size to obtain alumina powder of the desired particle size. The classification treatment can be performed by a technique such as sieving, air classification, elutriation, and / or centrifugation. The post-treatment may be performed as necessary. If the desired alumina powder can be obtained after firing, the post-treatment may be omitted.
[0063] In this manner, the plate-like alumina powder of the present embodiment can be produced. The obtained alumina powder contains many alumina particles having a desired size, a smooth surface, and a high degree of circularity. Therefore, the alumina powder has excellent dispersibility. Such alumina powder can be suitably used for various applications, including paints and cosmetics.
[0064] <<3. Paints and cosmetics>> The paint or cosmetic of this embodiment contains the above-mentioned plate-like alumina powder. The paint or cosmetic may contain the alumina powder alone or in a surface-treated form. The surface treatment may be performed by providing a surface treatment agent such as a silicon-based compound, an alkylsilane-based compound, and / or a fluorine-based compound on the particle surface of the plate-like alumina powder. The paint or cosmetic may contain a solvent or a resin in addition to the plate-like alumina powder. The solvent may be aqueous or non-aqueous. The paint or cosmetic may further contain known additives such as oils, pigments other than the plate-like alumina powder, fillers, surfactants, viscosity adjusters, preservatives, fragrances, moisturizers, bioactive ingredients, salts, chelating agents, neutralizing agents, and / or pH adjusters. EXAMPLES
[0065] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to the following examples.
[0066] (1) Preparation of plate-shaped alumina powder [Examples 1 to 6 and Comparative Examples 1 to 7] <Raw material mixing process> Aluminum hydroxide (gibbsite) powder (Nippon Light Metal Co., Ltd., BF013) was prepared as the alumina source for Examples 1 to 5 and Comparative Examples 1 to 7. Aluminum hydroxide (gibbsite) powder (Nippon Light Metal Co., Ltd., BE043) was prepared as the alumina source for Example 6. The properties of the prepared aluminum hydroxide powder are shown in Table 1 below. Note that Na2O shown in Table 1 is the total value of the eluted sodium content on and near the crystal surface of the aluminum hydroxide and the uneluted sodium content incorporated within the crystal lattice, and f-Na2O is only the eluted sodium content on and near the crystal surface of the aluminum hydroxide.
[0067] Separately, aluminum fluoride (DO-FLUORIDE CHEMICALS CO., LTD.; AlF3), silicon oxide (Marukama Kamado Toryo Co., Ltd., Yukijirushi Silica SP-3; SiO2), sodium carbonate (Kanto Chemical Co., Ltd.; Na2CO3), and sodium silicofluoride (Kanto Chemical Co., Ltd., sodium hexafluorosilicate; Na2SiF6) were prepared as additives.
[0068] Next, the prepared aluminum hydroxide powder and additives were mixed to prepare a raw material mixture. The amount of additives was adjusted so that the content ratio of each additive in the raw material mixture was the value shown in Table 1 below. Mixing was performed by putting the raw materials in a bag and shaking them (manual method; Examples 1, 2, 4, 5 and Comparative Examples 2 to 7) or by using a rocking mixer (mechanical method; Examples 3, 6 and Comparative Example 1).
[0069] <Firing process> The obtained raw material mixture was placed in a firing container, and the firing container was closed with a dedicated lid. The firing container with the lid was placed in a firing furnace and fired in the air. The firing was performed using an electric furnace or a shuttle kiln. During firing, the temperature was raised to the firing temperature at a heating rate of 100°C / hour, and then the temperature was maintained for 10 hours, and then the material was naturally cooled. The firing temperature was 1000°C (Comparative Example 7) or 1100°C (Examples 1 to 6 and Comparative Examples 1 to 6). After the temperature inside the furnace had completely dropped, the firing container was removed from the furnace, and the fired product (alumina) was collected.
[0070] <Post-treatment> For some samples (Examples 1 to 6, Comparative Examples 1, 2, 4, and 7), crushing treatment was performed. Wet crushing was carried out by adjusting the crushing strength so that the plate shape was not destroyed, and filtration treatment was performed to obtain the crushed product (alumina). Then, using a dryer, the obtained crushed product was dried at 105 °C overnight. Also, for some samples (Example 3, Comparative Example 1), removal of coarse and fine particles was performed after the crushing treatment.
[0071] In this way, plate-shaped alumina powders of Examples 1 to 6 and Comparative Examples 1 to 7 were produced. The production conditions of the plate-shaped alumina powder are summarized in Table 1 below.
[0072] [Table 1]
[0073] (2) Evaluation Using the alumina powders obtained in Examples 1 to 6 and Comparative Examples 1 to 7 as samples, evaluations of various properties were carried out as follows.
[0074] <Particle size distribution> The particle size distribution of the alumina powder was measured using a laser diffraction / scattering type particle size distribution measuring device (Nikkiso Co., Ltd., Microtrac MT3300). Specifically, the alumina powder was directly put into the inlet of the measuring device, dispersed for 1 minute by the dispersion function installed in the device, and then the particle size distribution was measured. The average particle diameter was determined as the particle diameter corresponding to an integrated particle size distribution rate of 50% by volume.
[0075] <SEM observation> The alumina powder was evaluated using a scanning electron microscope (JEOL Ltd., JSM-F100; SEM) and image analysis software (ImageJ). Specifically, an SEM image of the obtained alumina powder was taken, and the particles shown in the image were evaluated using ImageJ to measure the particle size and thickness, and the average particle size and average thickness were calculated. The average particle size was calculated as the average value of 80 particles, and the average thickness was calculated as the average value of 30 particles. The ratio of the average particle size to the average thickness (average particle size / average thickness) was calculated as the average aspect ratio.
[0076] <Crystal phase> The crystal phase of the alumina powder was examined using an X-ray diffractometer (Rigaku Corporation, RINT UltimaIII). Specifically, the obtained alumina powder was placed on a dedicated sample plate and gently spread to a size of 20 mm x 20 mm x 0.5 mm to prepare a measurement sample. Next, the X-ray diffraction pattern of the measurement sample was evaluated using the X-ray diffractometer. Then, it was examined whether a diffraction peak based on α-alumina (corundum phase) was detected in the obtained X-ray diffraction pattern.
[0077] <Component analysis> The component analysis was performed using a scanning X-ray fluorescence analyzer (Rigaku Corporation, ZSX PrimusIV). Specifically, alumina powder was placed in a platinum crucible and set in a high-frequency melting device. After that, the crucible was preheated at 700°C for 60 seconds, and then rocked at 1200°C for 120 seconds to produce a glass bead sample. The glass bead sample was then evaluated using the scanning X-ray analyzer. The obtained data was compared with the data of the standard sample for the calibration curve to obtain the evaluation results.
[0078] <Specific surface area> Specific surface area (S BET ) was evaluated by N2 gas adsorption method using a manual specific surface area measuring device (Micromeritics Instrument Corp., FlowSorbIII 2305 type).
[0079] <Image analysis of particles> Image analysis of the alumina particles contained in the alumina powder was performed to determine the proportion of highly circular particles. Specifically, a fully automated image-based particle size distribution analyzer (Spectris Corporation, Morphologi 4) was used to evaluate the particle morphology based on the two-dimensional projection image of each particle constituting the alumina powder. More specifically, the area (s) and perimeter (l) of each particle were measured in the two-dimensional projection image. Next, the perimeter (lc) of the equivalent area circle of this particle was calculated according to the following formula (1). The circularity of each particle was then calculated from the particle perimeter (l) and the equivalent area circle perimeter (lc) according to the following formula (2).
[0080]
number
[0081] The number of analyzed particles and the number of particles with a circularity of 0.953 or more (high circularity alumina particles) were counted, and the proportion of these numbers (number of high circularity alumina particles / number of analyzed alumina particles) was calculated as the proportion of high circularity particles.
[0082] <Zeta potential> The zeta potential of the alumina powder was measured. Specifically, the alumina powder dispersion (solvent: distilled water) was prepared by dispersing the alumina powder using a homogenizer (Nihon Seiki Seisakusho Co., Ltd., US-300T) at 300 W, 20 kHz, and 1 minute. The dispersion was then placed in a cell with electrodes and attached to a designated position of a zeta potential measuring device (Spectris Inc., Zetasizer Nano ZS). A voltage was applied to the dispersion, causing the alumina particles to electrophores. A laser beam was irradiated onto the cell, and the scattered light from the alumina particles was detected.
[0083] (3) Evaluation results The evaluation results obtained for Examples 1 to 6 and Comparative Examples 1 to 7 are summarized in Table 2 below.
[0084] The alumina powders of Examples 1 to 6, in which the composition and amount of additives were appropriate, had a high circularity particle ratio of 28% or more. In contrast, the alumina powders of Comparative Examples 1 to 7 had a low circularity particle ratio of 14% or less. A more detailed study revealed the following.
[0085] Comparing the results of Examples 3 and 4 and Comparative Examples 1 and 2, it was confirmed that when the amount of SiO2 added was 0.05 mass% or less or 0.20 mass% or more, which was outside the range of the appropriate amount, the particle shape was not disk-like but jagged, and the circularity was smaller than that of a hexagonal plate. From this, it was found that disk-like alumina particles with high circularity could be obtained by optimizing the amount of SiO2 added.
[0086] Comparing the results of Examples 3 and 5 and Comparative Example 1, it was found that disc-shaped alumina particles could be obtained by optimizing the amount of AlF3 added. However, if the amount of AlF3 added was too large, the particle size became small.
[0087] From the results of Comparative Example 3, it was confirmed that when the amount of SiO2 added to the amount of AlF3 added exceeded a certain ratio, α-alumina was no longer detected in the alumina powder. It is considered that the phase transition to α-alumina did not proceed and the alumina remained as transition alumina.
[0088] From the results of Comparative Example 4, it was confirmed that when only AlF3 was added and sintered, an alumina powder containing a mixture of spherical particles in addition to plate-like particles having a small particle size was obtained.
[0089] From the results of Comparative Examples 5 and 6, it was confirmed that when only SiO2 was added and fired, α-alumina was not detected because there was no AlF3 to promote the phase transition to α-alumina. The same was true when no additive was added, and α-alumina was not detected.
[0090] Comparing the results of Example 4 and Comparative Example 7, it was found that when the firing temperature was changed from 1100°C to 1000°C, the amount of heat applied to the raw material mixture during firing was insufficient, making it difficult for grain growth to proceed, and disc-shaped particles may not be obtained.
[0091] [Table 2]
[0092] A graph of the zeta potential measurement results obtained for the alumina powder of Example 6 is shown in FIG. 3. FIG. 3 also shows the zeta potential measurement results for commercially available plate-like polygonal alumina powders A and B. The graph shown in FIG. 3 shows the relationship between the zeta potential and the total scattering intensity. Here, the total scattering intensity is an amount that represents the amount of light or brightness of the scattered light from the particles. The properties of the alumina powder of Example 6 and the plate-like polygonal alumina powders A and B are shown in Table 3 below.
[0093] As shown in Fig. 3, the alumina powder of Example 6 had a higher total scattering intensity (amount of scattered light and brightness) than the plate-like polygonal alumina powders A and B. The alumina powder of Example 6 has almost the same particle size as the plate-like polygonal alumina powders A and B. Nevertheless, the result that the amount and brightness of the scattered light are high indicates that the alumina powder of Example 6 has excellent dispersibility.
[0094] [Table 3]
[0095] From the above results, it can be seen that the present embodiment provides a plate-like alumina powder with excellent dispersibility and a method for producing the same.
Claims
1. A plate-like alumina powder comprising a plurality of plate-like α-alumina particles, the plate-like alumina powder having an average particle size of 2 μm or more and 100 μm or less and an average thickness of 0.2 μm or more and 3.0 μm or less, The plate-like alumina powder has a number ratio (high circularity particle ratio) of particles having a circularity of 0.953 or more (high circularity alumina particles) of 25% or more when the plate-like alumina powder is analyzed by a dry particle image analyzer.
2. 2. The plate-like alumina powder according to claim 1, wherein the average particle diameter is 5 μm or more and 50 μm or less, the average thickness is 0.3 μm or more and 1.0 μm or less, and the proportion of high circularity particles is 40% or more.
3. Alkali metal (AM) 2 The silicon (Si) content is 0.01 mass % or more and 0.5 mass % or less in terms of O, and the silicon (Si) content is SiO 2 The plate-like alumina powder according to claim 1 , wherein the alkali metal (AM) is sodium (Na) in an amount of 0.01 mass % or more and 0.3 mass % or less in terms of alkali metal (AM) content.
4. A method for producing the plate-like alumina powder according to any one of claims 1 to 3, comprising the following steps: Preparing a raw material mixture containing aluminum hydroxide powder and an additive; and Firing the raw material mixture at a temperature of 900° C. or more and 1300° C. or less; Equipped with The raw material mixture is an alkali metal (AM) 2 O equivalent of 0.01 mass % or more and 0.5 mass % or less, silicon (Si) is SiO 2 and fluorine (F) in an amount of 0.1 to 5.0 mass% in terms of F, and the alkali metal (AM) is sodium (Na).
5. The additive is an alkali silicofluoride (AM 2 SiF 6 ), or aluminum fluoride (AlF 3 ) and silicon oxide (SiO 2 5. The method of claim 4, comprising:
6. The additive is an oxide of an alkali metal (AM). 2 O) and carbonate (AM 2 CO 3 6. The method of claim 5, further comprising one or both of:
7. A paint or cosmetic comprising the platelet alumina powder according to any one of claims 1 to 3.
Citation Information
Patent Citations
Method for comprehensively utilizing all components of high-calcium aluminosilicate mineral
CN113666403A
Superfine sphere-like alumina particles, and preparation method and application thereof
CN116282097A
Production of alpha-alumina powder
JP1995187663A
Alpha-alumina powder and its production
JP1995206430A
Alpha-alumina powder and its production
JP1996012322A